Progressive entanglement religious intimacy in Japanese-Filipino marriages - Lopez, Mario Ivan (Quezon City Ateneo de Manila University, 2012)
"Studies on international marriages often focus on how gender, sexuality, race, and ethnicity are constructed and articulated through the migration process. The influence of religion as one articulator in migrants' lives and its influence on the family tend to be ignored, but arguably individuals' faith must be included in the research agenda. Using ethnographic examples, this article traces the religious practices that develop in the lives of some Japanese-Filipino couples. This article highlights not just the transnational mobility of migrants, but also the movement of their faith and its potential impact on intimate relations within migrant homes and communities postmigration."
Keywords: Intermarriage; Internal migration -- Japanese; Conversion; Neoliberalism